Development of A Career Options Assessment for Intellectual Disability Students in The Extraordinary School of Padang - Jofipasi, Rendy Amora; Afdal, Afdal; Iswari , Mega; Efendi , Jon (Angstrom Centre of Education, 2024)
The objective of this research is to develop a career choice assessment tool that is useful for students intellectual disability and that is based on the personality type of the career of Holland in students intellectual disability. This research produces an assessment instrument based on the Saifuddin Azwar instrument development procedure. The study involved a intellectual disability teacher in the extraordinary School of Padang who was in class XI and XII. Testing the effectiveness of the product is carried out by conducting a confirmation factor analysis of the test results. The test results of the instrument show that the product test results meet the latent variable. Chi square value is 0.623 and RMSEA value is 0.032. These results indicate that the product has a good of fit. Therefore, it can be concluded that a well-made assessment tool is used to choose a career.